Current Issues in Assessment of Risks Related to Investment Projects - Sergeevich Voronov, Alexander; Vladimirovich Karmanov, Mikhail; Anatolievna Kiseleva, Irina; Ivanovich Kuznetsov, Vladimir; Sergeevna Leontieva, Lidia (International Journal of Engineering and Technology, 2018)
The definition of the essence of an object of management in economics is an indispensable component of professional risk management. Since the national risk management theory is just being formed, the need to find a clear and comprehensive definition for the notion "risks" is especially topical. Capital valuation is one of the most important issues, which needs to be solved by companies during ROI studies. This article makes an attempt to study the role of risk management in the implementation of investment projects. The main purpose of this article is to identify the main regularities which determine the peculiarities of risk assessment in business, being the key element facilitating the organization of investment projects. The objectives have been as follows: to review the basic concepts of risk management; to study its components in business; to reflect the system and risk management principles, and to carry out risk assessment; to consider the main kinds of risks in the business area.The article describes various types of investment and project risks, risk analysis methods for investment projects, as well as efficiency indicators of investment projects, and provides an analysis of risk factors and uncertainties during the development of investment projects. The peculiarities of the practical use of project risksâ€™ analysis methods have been studied. Risk assessment methods for an investment project help evaluate its feasibility, the time within which it will start being profitable, as well as the probabilistic volume of its future profits. Investment project valuation models have been analyzed, in particular, the CAPM model for emerging capital markets. The DCF method has been studied, being the base for assessing the attractiveness of business in general and a company's investment project in particular.Â Â